Effects of hormone replacement therapy alone or in combination with alendronate on bone mineral density of women with osteoporosis - Karzewnik, Ewa; Sewerynek, Ewa (Menopause Review/Przegląd Menopauzalny, 2005)
Hormone replacement therapy (HRT) alone as well as bisphosphanates alone are effective treatment for postmenopausal osteoporosis but the effect of multi-drugs treatment is not well recognized. The aim of the study was to compare HRT, and its combination with alendronate (ALE) on bone mineral density (BMD) in postmenopausal women with osteoporosis. Materials and Methods: A total of 90 patients with osteoporosis, who had not been receiving HRT for at least 1 year were randomized to receive 1 mg 17b-estradiol plus 0.5 mg 19-norethisterone acetate daily, per os (n=45; Group I), or in combination with ALE in a dose 10 mg/d (HRT+ALE; n=45; Group II), for 1 year. BMD of the lumbar spine was measured using QCT at baseline and after 1 year of treatment. Each group were divided into 2 subgroups depend on the T score values: A – 2.5 or less at the lumbar spine (n=37); B – higher than –2.5 in patients with additional risk factors (n=8). Results: At the end of one year treatment, increases in spinal BMD were found in all examined groups but statistically significant on combined therapy. Compared with HRT alone, ALE+HRT produced significantly greater increases in BMD of the lumbar spine [T score ALE+HRT vs HRT – Group A 8.26% vs 5.78% (NS); Group B 13.8% vs 10.18% (NS) or BMD – Group A 3,24% vs 1.40% (NS); Grupa B 3.35% vs 0.74% (NS) ]. Conclusion: The combination of HRT and ALE in postmenopausal women with osteoporosis did not offer an extra gain of BMD over treatment of HRT alone.